The Trans-Java Toll Road as Neoliberal Spatial Fix: Economic Restructuring and MSME Marginalization - Naim, Chanif (Advanced Studies on Socio-Economy Development, 2025)
This article critically examines the socio-spatial impact of the Trans-Java Toll Road on Java's northern coastal region, also known in Indonesian as Pantura, with a focus on micro, small, and medium enterprises (MSMEs). While promoted as a solution for improving logistics and economic growth, the toll road exemplifies a neoliberal spatial fix that unevenly redistributes development. Drawing on David Harvey's concepts of